Hipon at biya - Pacis, Carla; Joanne de Leon (Quezon City, Philippines : Adarna House Inc., 2004)
On the white sand of a coral reef lived Hipon and Biya. Although there were not the same sort, they lived happily together.
Keywords: CHILDREN STORIES